2017
DOI: 10.1186/s13099-017-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Capsular polysaccharide inhibits adhesion of Bifidobacterium longum 105-A to enterocyte-like Caco-2 cells and phagocytosis by macrophages

Abstract: Background Bifidobacterium longum 105-A produces markedly high amounts of capsular polysaccharides (CPS) and exopolysaccharides (EPS) that should play distinct roles in bacterial–host interactions. To identify the biological function of B. longum 105-A CPS/EPS, we carried out an informatics survey of the genome and identified the EPS-encoding genetic locus of B. longum 105-A that is responsible for the production of CPS/EPS. The role of CPS/EPS in the adaptation to gut tract environment and bacteria-gut cell i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 102 publications
2
27
0
4
Order By: Relevance
“…More studies are needed expand the known lexicon of bacterial polysaccharide-immune system interactions, and they may even lead to the discovery of new, bioactive CPS for potential use as therapeutics to improve human health. (13,26,29,30,32,34,41,45,49,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More studies are needed expand the known lexicon of bacterial polysaccharide-immune system interactions, and they may even lead to the discovery of new, bioactive CPS for potential use as therapeutics to improve human health. (13,26,29,30,32,34,41,45,49,53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, innate immune phagocytes cultured with B. thetaiotaomicron expressing antistimulatory CPSs were poor antigen presenters to the adaptive immune system. Bifidobacterium longum's EPS also inhibited macrophage phagocytosis (32). In contrast, other MPGs can promote the maturation of innate immune cells so that they serve as better antigen presenting cells (APCs) to the adaptive immune system.…”
Section: Mpgs Modulate Innate Immune Responses In the Intestinementioning
confidence: 99%
“…To colonize the gut, the bacteria have to first withstand the harsh conditions of the stomach and then grow and multiply in the duodenum and colon, in the presence of bile salts. In Bifidobacterium longum , capsule expression would enhance survival in the stomach and allow growth under high concentrations of detergent-like bile salts in the duodenum [ 65 ]. Similarly, a study performed in yeast has shown that although capsules from environmental and pathogenic strains display similar composition and features, they fulfil different roles [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the function of these genes has been mostly proposed by means of in silico analyses after homology comparison with the information held in genetic databases (Hidalgo-Cantabrana et al, 2014 ; Ferrario et al, 2016 ; Jiang and Yang, 2018 ). For only a few genes has the function been demonstrated by means of functional assays; examples of functionally characterized eps genes include the GTF (Lamothe et al, 2002 ) also the priming-GTF (Lebeer et al, 2009 ; Fanning et al, 2012 ; Tahoun et al, 2017 ), chain-length determining genes (Bouazzaoui and LaPointe, 2006 ; Hidalgo-Cantabrana et al, 2015 ), and transcriptional regulators of the eps operons (Dertli et al, 2016 ).…”
Section: Genetics and Synthesis Of Eps In Bifidobacterium mentioning
confidence: 99%